Performance and grazing behavior of growing goats supplemented with palm tree fruit - Garcez, Bruno Spindola; Alves, Arnaud Azevêdo; Araújo, Daniel Louçana da Costa; Oliveira, Maria Elizabete de; Pompeu, Roberto Cláudio Fernandes Franco; Rogério, Marcos Cláudio Pinheiro; Moreira, Antônia Leidiana; Lima, Isak Samir de Sousa (Brazilian Journal of Animal Science, 2019)
This study aimed to evaluate the performance and ingestive behavior of growing goats grazing on Tanzania guinea grass and fed diets containing 40% carnauba or tucum fruits. Twenty-one male castrated goats were distributed into three groups, one exclusively on pasture and the other two on pasture and fed diet supplemented at the level of 1.5% body weight (BW) in a completely randomized design. The intake of the supplements was obtained by difference between the amount supplied and the leftovers, with weighing performed every seven days, while pasture intake was determined using titanium dioxide (TiO2 ) as external indicator. Ingestive behavior was evaluated for three days. The supplement containing carnauba fruit resulted in a greater intake of neutral detergent fiber (0.137 kg NDF/day), with a reduction of 8.61% in the pasture dry matter (DM) intake of goats. Associated with the intake of pasture nutrients, the tucum fruit diet met the protein (0.103 kg CP/day) and energetic (0.547 kg TDN/day) requirements of goats with intake set at 0.124 kg CP/day and 0.572 kg TDN/day, with higher weight gain (0.111 kg/day) and larger loin eye area (12.76 cm2 ). The supplementation with fruits influenced the grazing behavior of goats, increasing the idle time by 1 h in relation to animals not supplemented. The supplementation of growing goats grazing on Tanzania guinea grass pasture with a diet containing 40% tucum fruit, in the proportion of 1.5% BW, did not meet the nutritional requirements for gain of 150 g/day; however, it met requirements for maintenance and average gain of 111 g/day. Energy supplementation reduces the grazing time of goats; thus, it is necessary to consider the level and formulation of supplements, with the possibility of increasing the stocking rate and productivity per unit area
Keywords: Bactris setosa; bite rate; Copernicia prunifera; pasture supplementation; weight gain